2020
DOI: 10.1080/07481187.2020.1829747
|View full text |Cite
|
Sign up to set email alerts
|

Children’s experiences of the family talk intervention when a parent is cared for in palliative home care—A feasibility study

Abstract: The aim of this study was to explore the feasibility of the family talk intervention (FTI) and its acceptability to dependent children when a parent is cared for in palliative home care. The main goal of FTI is to increase family communication about the illness. The present paper derives from a pilot study and is based on 25 children's reports, involving both questionnaires and interviews, after participation. A majority of the children appreciated the structure and content of FTI. They felt seen, heard, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 42 publications
5
10
0
1
Order By: Relevance
“…positively by both parents and children in adult care (palliative care and cancer care) regarding both structure and content. 20,22,29 Alvariza, Jalmsell 20 found that parents reported that FTI was well-structured and flexible regarding their family's needs, which is in line with this study. Moreover, almost all parents and children recommended FTI to other families, 20,29 which was also found in this study.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…positively by both parents and children in adult care (palliative care and cancer care) regarding both structure and content. 20,22,29 Alvariza, Jalmsell 20 found that parents reported that FTI was well-structured and flexible regarding their family's needs, which is in line with this study. Moreover, almost all parents and children recommended FTI to other families, 20,29 which was also found in this study.…”
Section: Discussionsupporting
confidence: 86%
“…The lack of support might also have influenced the very positive experiences of FTI and the suggestion that this should be a standard of care. FTI has been experienced positively by both parents and children in adult care (palliative care and cancer care) regarding both structure and content 20,22,29 . Alvariza, Jalmsell 20 found that parents reported that FTI was well‐structured and flexible regarding their family's needs, which is in line with this study.…”
Section: Discussionsupporting
confidence: 84%
“…A few siblings reported problems related to the order of the FTI meetings, which in their opinion led to the interventionists making assumptions about them that they were not comfortable with. This has been highlighted in earlier evaluations of FTI in other contexts 28 . Siblings generally felt they had “a say” in how long their meetings with the interventionist should be, the location, and if a parent should be included.…”
Section: Discussionmentioning
confidence: 91%
“…The information must also be age‐appropriate (Semmens & Peric, 1995) and be given on the children and adolescents’ own terms (Dehlin & Reg, 2009). Although the need for information is generally great among children and adolescents, some prefer not to know everything while some said that they had received information they did not want to know (Dehlin & Reg, 2009; Eklund, Jalmsell, et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies emphasized that information should be provided by HCPs (Alvariza et al., 2017; Berman et al., 1988; Bylund‐Grenklo et al., 2015; Christ et al., 1994; Karlsson et al., 2013; Tillquist et al., 2016). However, children and adolescents stressed that they preferred talking to experienced HCP well‐trained in communication (Eklund, Jalmsell, et al., 2020).…”
Section: Resultsmentioning
confidence: 99%